2019
DOI: 10.1039/c8tc05696j
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of 4-n-octyl-4′-cyanobiphenyl molecules on graphene oxide surface via electron–phonon interaction and its applications in nonlinear electronics

Abstract: Molecular arrangement of 8CB on the GO surface and its I–V curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…This postulate is recently reported by us [23]. For the intermediate dispersion concentration of 2D-GO nanoflakes, the orientation of 8CB molecules represents a merged state of the planar and homeotropic orientations.…”
Section: Polarized Optical Microscopic Studysupporting
confidence: 80%
See 4 more Smart Citations
“…This postulate is recently reported by us [23]. For the intermediate dispersion concentration of 2D-GO nanoflakes, the orientation of 8CB molecules represents a merged state of the planar and homeotropic orientations.…”
Section: Polarized Optical Microscopic Studysupporting
confidence: 80%
“…The temperature for recording the POMs of 8CB/GO composites in a desired phase was chosen from their corresponding phase schemes. It is observed that the presence of 2D-GO flakes significantly changes the molecular orientation of the 8CB; as a result, the exemplary optical textures of the SmA and N phases have not been observed for the composites because of the GO flakes migrate closer to ITO substrate/LC interface due to viscous drift [23].…”
Section: Polarized Optical Microscopic Studymentioning
confidence: 99%
See 3 more Smart Citations